An exploration into how Grade 3 Foundation Phase teachers implement differentiated instructional practices in their mathematics classrooms - Jack, Nomzamo Bridget (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
Today's teaching space is more diverse than before. As a result, differentiated instruction is considered helpful in supporting learner diversity. This teaching approach considers socio-cultural, multiple intelligences, and learning styles also termed learning preferences of learners. It is against this view that I wanted to investigate the implementation of differentiated instruction teaching practices in the Foundation Phase. This study explored differentiated teaching strategies and procedures in mathematics teaching, and I observed four Grade 3 teachers. The theoretical framework underlying this study was the theory of practice architectures. This study is located within an interpretivist paradigm within which I employed a case study research design. The collection of the data sets was through observations and semi-structured interviews. For an analysis of observations, I used a deductive approach. On the other hand, for the semi-structured interviews, I use an inductive approach to discover patterns and themes that I applied during the data analysis process. The validation process was done by giving interview transcripts and a summary of discussions to respondents to verify their responses and check for any misinterpretations. Rich data sets were analysed concerning the research questions, which were as follows: What are the current differentiated instruction teaching practices used by Grade 3 Mathematics teachers? How can the teachers' differentiated instruction teaching practices be understood in terms of doings, sayings and relatings? How are differentiated instruction teaching practices made visible through the lens of the Theory of Practice Architecture? The findings from the study revealed that the use of learners' everyday language influences their understanding of mathematics terminology. The study discovered that learners were more comfortable using English to make sense of mathematics terms instead of using isiXhosa, the Language of Learning and Teaching in the Foundation Phase. Additionally, linking learning to learners' everyday English language enabled them to learn mathematics terms in a relaxed and non-threatening situation, while isiXhosa seemed to constrain learning. Further, the findings revealed that teachers were unclear about differentiated instruction. That was evident when they did not know the elements of differentiated instruction. Thus, the study recommends that teachers need to be supported through workshops to enable them to enact differentiated instruction in their teaching.
Keywords: Mathematics-- Study and teaching (Elementary) -- South Africa; Differentiated instruction; Inclusive education; Mathematics teachers Training of; English-medium instruction